The Design and Experimentation of a Wing-Shaped Stubble-Breaking Device for Maize Stubbles - Xuanting Liu; Hongyan Qi; Shuo Wang; Zihe Xu; Peng Gao; Daping Fu; Yunhai Ma (Agriculture)
To achieve high-quality no-till seeding, a wing-shaped stubble-breaking device with excellent stubble-breaking performance was designed for maize stubble. A model of maize stubble was developed based on the Discrete Element Method (DEM) and verified through soil bin tests. The DEM model was used to optimize the design parameters of the device and to investigate the interaction between the blades and the maize stubble during the stubble-breaking process. Field experiments were conducted to evaluate the performance of the device. The results indicated that the DEM model was accurate; when the optimal design parameters of the wing-shaped stubble-breaking device were a 37° slide cutting angle, 31° pitching angle, and 50 mm wing width, the average torque was 41.26 N·m, the soil breakage rate was 85.68%, and the soil backfill rate was 71.65%; the wing-shaped stubble-breaking device could separate the inside and outside of the strip tillage area and cut maize stubbles and soil blocks twice, thus having excellent stubble-breaking performance. This study provided an effective and feasible method for designing stubble-breaking devices and studying the interaction between blades, soil, and roots, which improved soil tillage theory and was beneficial in promoting conservation tillage technology.